ПРОБЛЕМЫ КУЛЬТУРЫ РЕЧИ И ЯЗЫКОВОГО ЭТИКЕТА МОЛОДЕЖИ В КАЗАХСКОЯЗЫЧНОМ ИНТЕРНЕТ ПРОСТРАНСТВЕ - Әміржанова, Назира ("МӘҢГІЛІК ЕЛДІҢ МӘҢГІЛІК ТІЛІ" Халықаралық симпозиум материалдары/ THE ETERNAL LANGUAGE OF THE ETERNAL NATION international symposium, 2016)
Появление всемирной сети как неисчерпаемого источника информации позволило использовать ее не только в качестве инструмента для познания, но и как средство для обшения. Казахский интернет способствует поднятию интеллектуального потенциала страны, расширению поля государственного языка, и дает нашим соотечественникам из дальнего и ближнего зарубежья огромную возможность устанавливать связь в общей информационной системе. It is definite that million Kazakh language information changers that satisfy the Kazakh internet filled up by different web-sites that answer to social demand year by year. Kazakh internet is giving possibility to increase intellectual potency, extending the area of state language to make connection of native people in distant and near foreign countries in general mass system, but there is a worry about that the users of mass space have not kept the system of orthographic rule of language in connection and there is a wide process of signing the linguistic units according to orthoepic regularities. It is definite that this process influences on coming of "negative graphic portrait" instead of "positive graphic portrait" in linguistic consciousness of Internet users. Therefore, it can be known as an actual problem that needs investigation at present time differences in graphic decoration of written language forming in virtual world.
Keywords: проблемы культуры речи и языкового этикета; kazakh language information; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education